CLSM: COUPLE LAYERED SECURITY MODEL A HIGH-CAPACITY DATA HIDING SCHEME USING WITH STEGANOGRAPHY - Kocak, Cemal (Image Analysis and Stereology, 2017)
Cryptography and steganography are the two significant techniques used in secrecy of communications and in safe message transfer. In this study CLSM – Couple Layered Security Model is suggested which has a hybrid structure enhancing information security using features of cryptography and steganography. In CLSM system; the information which has been initially cryptographically encrypted is steganographically embedded in an image at the next step. The information is encrypted by means of a Text Keyword consisting of maximum 16 digits determined by the user in cryptography method. Similarly, the encrypted information is processed, during the embedding stage, using a 16 digit pin (I-PIN) which is determined again by the user. The carrier images utilized in the study have been determined as 24 bit/pixel colour. Utilization of images in .jpeg, .tiff, .pnp format has also been provided. The performance of the CLSM method has been evaluated according to the objective quality measurement criteria of PSNR-dB (Peak Signal-to-Noise Ratio) and SSIM (Structural Similarity Index). In the study, 12 different sized information between 1000 and 609,129 bits were embedded into images. Between 34.14 and 65.8 dB PSNR values and between 0.989 and 0.999 SSIM values were obtained. CLSM showed better results compared to Pixel Value Differencing (PVD) method, Simulated Annealing (SA) Algorithm and Mix column transform based on irreducible polynomial mathematics methods.